Involuções sobre álgebras de grupo semisimples - Robson Willians Vinciguerra (2009)
In this work we present necessary and sufficient conditions for which the canonical involution of the group algebra K[G] induces an involution of the first kind on each simple component of K[G]. If the conditions are satisfied and K is a real closed field, then we give an improved version of Theorem 13.3 of Scharlau [12]